Jesus and the Law - Crossley, James G. (Journal for the study of the historical Jesus, 2015)
This essay takes an appreciative look at the influence of E. P. Sanders’s work on Jesus, Judaism and the Law and attempts to develop some of Sanders-style critique of scholarship to his ongoing influence. Particular attention is paid to Mt. 8.21–22/Lk. 9.59–60, Mk 2.23-28, and Mk 7.1-23. This article analyzes N. T. Wright’s domestication of Sanders’ criticism of anti-Jewish tendencies in scholarship, particularly where Wright uses Sanders to perpetuate the old myth of superiority over Judaism. This article also looks at how the influence of Hengel and Bultmann could continue through the credible endorsement of Sanders. Further consideration is given to the problematic notion of ‘conflict’ in the Gospel tradition.